On the importance of inheritance and development of Traditional Chinese Medicine nursing (论中医护理传承发展的重要性) - LI Suqian (李苏茜); TANG Ling (唐玲); E Haiyan (鄂海燕); CHEN Hong (陈宏); DENG Jianhua (邓建华); ZHOU Jie (周洁); LI Ye (李野) (Journal of International Translational Medicine Limited, 2022)
The combination of inheritance and innovation is the fundamental way to continue the cause of Traditional Chinese Medicine (TCM). As an important part of TCM, TCM nursing has gradually matured its inheritance mode of academic thinking and clinical experience. This article introduces the establishment of Chinese medicine colleges, the establishment of Chinese medicine hospitals, higher education of Chinese medicine nursing, the development of TCM nursing management mode, the development of TCM nursing work mode, the development of TCM nursing technology, and the establishment of TCM nursing inheritance studio. The purpose is to enable the majority of TCM nursing workers to have a deeper understanding of TCM nursing through this discussion, so as to make continuous progress for the inheritance and development of TCM nursing. (传承与创新相结合是延续中医药事业的根本途径, 中医护理作为中医药的重要组成部分, 其学术思想和临床经验的传承模式已日渐成熟。本文从中医院校的成立、中医医院的成立、中医护理高等教育、中医护理管理模式的发展、中医护理工作模式的发展、中医护理技术的发展、中医护理传承工作室的建立7个方面进行介绍, 旨在使广大中医护理工作者对中医护理有更深入的了解, 从而为中医护理传承发展而不断进取。)